Faktor-Faktor yang Berhubungan dengan Kepatuhan Membayar Premi Peserta BPJS Mandiri di Wilayah Kecamatan Kendari Barat Tahun 2023 - Kanna, Andi Multazam Nirwana; Yuniar, Nani; Liaran, Rastika Dwiyanti (Universitas Malahayati, 2024)
ABSTRACT National Health Insurance (Jaminan Kesehatan Nasional or JKN) is a government initiative in Indonesia aimed at improving public health by mandating the entire population to become participants. Despite the total number of JKN participants reaching 208,054,199 according to data from the Center for Data and Information of the Ministry of Health of the Republic of Indonesia (PUSDATIN KEMKES RI) in 2023, compliance with payment, especially for individual participants, remains a challenge. The city of Kendari records a total of 67,375 individual JKN participants with a total arrearage of IDR 33,266,604,994 in the same year. This serves as an important reference for researchers to determine whether factors are related to the compliance of individual BPJS participants in paying premiums. This research is a quantitative study with an analytical-observational approach and a cross-sectional design in the West Kendari sub-district, Kota Kendari, identified as the area with the highest arrearage rate. The study population includes all individual BPJS participants in the sub-district, with a sample size of 261 households (KK) selected using the Accidental Sampling technique. Data were collected through questionnaires. The research results indicate a significant relationship between respondents' occupations, premium increases, and payment procedure with the compliance of individual BPJS participants in paying JKN Health BPJS premiums (each with a significance value of 0.000, 0.001, and 0.002). However, there is no significant relationship between income and the perception of payment deadlines on the compliance of individual BPJS participants in paying JKN Health BPJS premiums (each with a significance value of 0.582 and 0.130). There is a correlation between occupation, premium increases, and payment procedure with the compliance in paying premiums by individual participants of BPJS in the West Kendari Sub-district area in 2023. Keywords: Compliance Relationship with Paying Dues ABSTRAK Dengan mewajibkan seluruh masyarakat untuk berpartisipasi, inisiatif pemerintah Indonesia Jaminan Kesehatan Nasional (JKN) bertujuan untuk meningkatkan kesehatan masyarakat. Meskipun jumlah peserta JKN mencapai 208.054.199 jiwa pada tahun 2023 menurut Pusat Data dan Informasi Kementrian Kesehatan Republik Indonesia (PUSDATIN KEMKES RI), kepatuhan pembayaran iuran bagi peserta mandiri masih menjadi masalah. Pada tahun yang sama, ada 67.375 peserta JKN Mandiri di Kota Kendari, dan tunggakan total mencapai Rp. 33.266.604.994. Hal ini sangat berguna bagi para peneliti untuk menentukan apakah ada faktor-faktor yang berkontribusi pada kepatuhan peserta BPJS Mandiri untuk membayar iuran mereka. Penelitian ini merupakan penelitian kuantitatif dengan pendekatan analitik-observasional dan desain cross-sectional di kecamatan Kendari Barat, Kota Kendari, sebagai wilayah dengan tingkat tunggakan iuran terbanyak. Populasi penelitian melibatkan seluruh peserta BPJS Mandiri di kecamatan tersebut, dengan sampel sebanyak 261 Kepala Keluarga (KK) menggunakan teknik Accidental Sampling. Data dikumpulkan melalui kuesioner. Hasil penelitian menunjukkan hubungan yang signifikan antara pekerjaan responden, kenaikan iuran, dan prosedur pembayaran iuran dengan kepatuhan peserta BPJS Mandiri membayar iuran BPJS Kesehatan (masing-masing dengan nilai signifikansi 0,000, 0,001, dan 0,002). Namun, tidak ada korelasi yang signifikan antara pendapatan dan persepsi batas waktu pembayaran terhadap kepatuhan peserta BPJS Mandiri membayar iuran BPJS Kesehatan. Kepatuhan pembayaran premi peserta BPJS mandiri di Wilayah Kecamatan Kendari Barat tahun 2023 berhubungan dengan pekerjaan, kenaikan iuran, dan proses pembayaran iuran. Kata Kunci: Hubungan Kepatuhan Membayar Iuran